'Two-step' percutaneous procedure for repairing the atrial septal defect with severe pulmonary hypertension: a case report. Issue 1 (10th January 2023) - Fu, Liang; Wang, Ruoxin; Zhao, Jinlong; Ni, Yinkai; Chen, Zonghui; Li, Feng
Abstract: Atrial septal defect is the most common type of congenital heart disease. Interventional closure is currently the best treatment for the atrial septal defect. However, the repair strategy for atrial septal defect accompanies by severe pulmonary hypertension remains controversial. We report a case of an atrial septal defect with severe pulmonary hypertension in which we applied a perforated occlude for atrial septal defect percutaneously at first. After 6 months, when the pulmonary pressure gradually went down, we completely blocked the reserved hole with a closure device percutaneously. We suggest that the stepwise procedure is an important treatment option for select patients with atrial septal defect accompanied by severe pulmonary hypertension.